The Sea Garden in Burgas between a City Brand and a Construct of Local Identity: City Nature as Ideology, Place, Memory (Seminar_BG, 2025)
The image of the central city park is associated with positive connotations – a “meeting” of nature and culture in the city, a symbol of modernity and prosperity. Its presence and maintenance are considered a sign of high city culture, but looking beneath this surface, we discover a distinctly dual, contradictory essence: in spatial terms, the park is a component of the urban environment, which, artificially constructed according to pre-planned boundaries, is “provided” to local residents as a free, physical, “natural” space for various activities. In its socio-cultural aspect, the park is embodying a specific ideology; an independent topographical center, loaded with multi-layered symbolic messages and imposing its own rules and uses. Referring to Lefebvre’s theory on the production of space, the article analyzes the Sea Garden in the city of Burgas in the following contexts: as a physical (material), imagined (mental) and social (experienced) space and the way in which they interact through the “local government - citizens” relationship. It addresses how the city government balances the sought-after city brand and the cultural meanings constructed by Burgas residents of local identity and memory. ReferencesApostolov, Ap. (2008). Zelenata sistema na Burgas. Burgas: Libra Skorp.Azuma, A. M., Gotlieb, R. B., Vallianatos, M., Gudmundson, J. K., Shafer, A. L., and Dreier, P. (2006). Connecting the Parks to the Community and the Community to the Parks. A Report to California State Parks and the California Coastal Conservancy. Los Angeles: Urban & Environmental Policy Institute at Occidental College.Basso, K. H. (1996). Wisdom Sits in Places: Landscape and Language Among the Western Apache. Albuquerque: University of New Mexico Press.Ditchev, I. (2005). Prostranstva na zhelanieto, zhelania za prostranstvo. Sofia: Iztok-Zapad.Halbwachs, M.  (1996). Kolektivnata pamet. Sofia: Kritika i humanizam.Lefebvre, H. (1991 [1974]). The production of space. Oxford: Basil Blackwell.Massey, D. (1995). Places and their pasts. History Workshop Journal, 39: 182-192.Nikolov, St. (2008). Otnovo moyat malak svyat – Burgas. Burgas: Bozhich.Raev, G. (1991). „Bulevardat“. Chernomorski far, 5 (88), 30.05.1991.Raychevski, St. (2011). Stariyat Burgas. Sofia: Zahariy Stoyanov.Simeonov, D. (2008). Burgas – pogled otvatre. Burgas: Znatsi.Wiedmann, F., and Salama, A. M. (2012). The role of architecture in producing urban qualities for sustainability: Implications for the future of architectural education. In The Proceedings of The Malaysia Architectural Education Conference (pp. 20-26). Serdang: Universiti Putra Malaysia.
Keywords: nature; culture; city park; Sea garden; Burgas; memory; place; brand